2012
DOI: 10.3233/jad-2012-111934
|View full text |Cite
|
Sign up to set email alerts
|

Early Onset Alzheimer's Disease is Associated with a Distinct Neuropsychological Profile

Abstract: Alzheimer's disease (AD) in younger patients is associated with a higher prevalence of atypical symptoms. We examined neuropsychological performance according to age-at-onset. We assessed cognition in 172 patients with AD (81 early and 91 late onset) in five cognitive domains (memory, language, visuo-spatial functioning, executive functioning, attention). Dementia severity was assessed using the Mini-Mental State Examination (MMSE) and global cognitive decline using Cambridge Cognitive Examination (CAMCOG). An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
117
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(127 citation statements)
references
References 32 publications
7
117
2
1
Order By: Relevance
“…The subgroups of AD patients were classified based on a determined cut-off of 65 years of age at onset, based on previous studies comparing features of EOAD and LOAD patients (Kemp et al, 2003;Kim et al, 2005;Shiino et al, 2006;Frisoni et al, 2007;Rabinovici et al, 2010;Canu et al, 2012;Sa et al, 2012;Smits et al, 2012;Cho et al, 2013), as well as on clinical grounds (Amaducci et al, 1986). This cut-off is also used in the DSM-IV TR nomenclature to specify subtypes (American Psychiatric Association, 2000).…”
Section: Subjectsmentioning
confidence: 99%
See 4 more Smart Citations
“…The subgroups of AD patients were classified based on a determined cut-off of 65 years of age at onset, based on previous studies comparing features of EOAD and LOAD patients (Kemp et al, 2003;Kim et al, 2005;Shiino et al, 2006;Frisoni et al, 2007;Rabinovici et al, 2010;Canu et al, 2012;Sa et al, 2012;Smits et al, 2012;Cho et al, 2013), as well as on clinical grounds (Amaducci et al, 1986). This cut-off is also used in the DSM-IV TR nomenclature to specify subtypes (American Psychiatric Association, 2000).…”
Section: Subjectsmentioning
confidence: 99%
“…Several studies also found that language function was more altered in early-onset patients (Chui et al, 1985;Filley et al, 1986;Becker et al, 1988;Faber-Langendoen et al, 1988;Binetti et al, 1996;Imamura et al, 1998), even when factors such as education and severity of dementia were controlled for, while variable findings were reported regarding the presence of apraxia (Seltzer and Sherwin, 1983;Reid et al, 1996). A more recent neuropsychological study reported that mildly demented EOAD patients performed worse than LOAD patients on visuospatial functioning, executive functioning, and attention, while memory was remarkably preserved (Smits et al, 2012). Other studies have also reported that early-onset patients have significant visuospatial difficulties when compared to late-onset patients Koedam et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations